CSF3 Is a Potential Drug Target for the Treatment of COVID-19 - Fang, Chao; Mei, Jie; Tian, Huixiang; Liou, Yu-Ligh; Rong, Dingchao; Zhang, Wei; Liao, Qianjin; Wu, Nayiyuan (Frontiers in Physiology, 2021)
Corona Virus Disease 2019 (COVID-19) is an acute respiratory infectious disease that appeared at the end of 2019. As of July 2020, the cumulative number of infections and death have exceeded 15 million and 630,000, respectively. And the new cases are increasing. There are still many difficulties in the research of mechanism and the development of therapeutic vaccines. It is urgent to explore the pathogenic mechanism of viruses to help prevent and treat COVID-19. In our study, we downloaded 2 datasets related to COVID-19 (GSE150819 and GSE147507). By analyzing the high-throughput expression matrix of uninfected human bronchial organoids and infected human bronchial organoids in the GSE150819, 456 differentially expressed genes (DEGs) were identified, which mainly enriched in cytokine-cytokine receptor interaction pathway and so on. And we constructed the protein–protein interaction (PPI) network of DEGs to identify the hub genes. Then we analyzed GSE147507, which contained lung adenocarcinoma cell lines (A549 and Calu3) and primary bronchial epithelial cell line (NHBE), obtaining 799, 460 and 46 DEGs, respectively. The results showed that in human bronchial organoids, A549, Calu3 and NHBE samples with SARS-CoV-2 infected, there was only an upregulated gene CSF3 was identified. Interestingly, CSF3 is one of the hub genes we previously screened in GSE150819, suggesting that CSF3 may be a potential drug target. Further, we screened potential drugs targeting CSF3 by MOE, the top 50 drugs were screened by flexible docking and rigid docking respectively, with 37 intersections, two antiviral drugs (Elbasvir and Ritonavir) were included, Elbasvir and Ritonavir formed van der Waals (VDW) interactions with surrounding residues to the binding with CSF3, and Elbasvir and Ritonavir significantly inhibited the CSF3 protein expression.